2000
DOI: 10.1046/j.1420-9101.2000.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

High-prevalence male-killing Wolbachia in the butterfly Acraea encedana

Abstract: Inherited bacteria which kill males during early development are widely distributed throughout the insects, but have been little studied outside of a single family of beetles, the Coccinellidae. We have investigated a male‐killing bacterium discovered in the butterfly Acraea encedana. This bacterium belongs to the genus Wolbachia and is identical in wsp gene sequence to a male‐killer in the closely related butterfly A. encedon, suggesting that it has either recently moved between host species or was inherited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 32 publications
2
93
0
1
Order By: Relevance
“…This phenomenon has been reported in Lepidoptera [27], Coleoptera, Diptera and Pseudoscorpiones [4]. This is undisruptive to the bacterium, because its transmission is favor by female and helps in its spreading.…”
Section: Phenotypic Effects Of Wolbachia Induce In Their Hostsmentioning
confidence: 68%
“…This phenomenon has been reported in Lepidoptera [27], Coleoptera, Diptera and Pseudoscorpiones [4]. This is undisruptive to the bacterium, because its transmission is favor by female and helps in its spreading.…”
Section: Phenotypic Effects Of Wolbachia Induce In Their Hostsmentioning
confidence: 68%
“…Under cytoplasmic inheritance, sex is determined by intracellular parasites (or other selfish genetic elements) that distort the sex ratio toward the transmitting sex, usually the female (Bull 1983). Theoretical models indicate that cytoplasmic sex factors can eventually cause the extinction of the nontransmitting sex (Hamilton 1967;Hatcher et al 1999) and extremely female-biased sex ratios have been found in natural populations (Jiggins et al 2000).…”
Section: Cytoplasmic Inheritance Of Sex Factorsmentioning
confidence: 99%
“…This suggests that the vertical transmission of these bacteria is a function of the male-killers themselves, not of their host. Conversely, in two species of butterfly, Acraea encedon and Acraea encedana, both of which are infected with the same strain of Wolbachia (showing no difference in over 5000 nuclear and mitochondrial nucleotides sequenced), vertical transmission efficiencies of 1.0 and 0.96 respectively have been recorded (Jiggins et al, 1998(Jiggins et al, , 2000(Jiggins et al, , 2001. Here, the vertical transmission appears to be host dependent.…”
Section: Selection On Host Nuclear Genomes: Vertical Transmission Sumentioning
confidence: 81%